Complicated forms of ulcerative colitis and Crohn’s disease (Diagnostic and Treatment Tactics) - Kaja L. Sigrid, Linnaea H. Marvie, Beaumont W. Averill (Academic Journal of Clinicians, 2023)
Complicated forms of ulcerative colitis and Crohn’s disease (Diagnostic and Treatment Tactics)